The role of digitization in revitalizing the course system at Northern Technical University - Duha Al-Malah; Enaam Sultan; Yahya Ibrahim; Ahmed El Shalawy (College of Education for Pure Sciences, 2022)
Northern Technical university in Iraq relied in their education on the course system, this system was characterized by some kind of difficulties. A questionnaire was distributed to professors, technicians, administrators, and students subject to the curriculum system as a secondary source for collecting data and information. The study found that NTU as a young and modern university has an infrastructure supported by an electronic educational administrative information system, It provides an integrated digital platform for teachers to participate extensively in lectures, courses, scientific and practical workshops, create interactive lessons, create assignments, tests and assessment through a solid and efficient platform that facilitated the student to complete his homework and duties in the time available to him by notifying them and informing them by sending an email that includes educational content and information and communication technology urged the university to continue with the course system. The study dealt with data analysis using structural equation modeling and the confirmatory factor analysis strategy as a means to measure the observational variables represented by the digitization axes, which in turn matched the measures of statistical analysis Amos.